1986
DOI: 10.1136/jnnp.49.8.874
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed primary intracranial neoplasms in pregnant women: a population-based assessment.

Abstract: SUMMARY The presence of a pregnancy at the time of the initial diagnosis of an intracranial neoplasm was studied using material from a population-based tumour registry. Seventeen malignant neoplasms of the brain (ICD 191), three meningiomas, three acoustic neurinomas and a pituitary adenoma associated with pregnancy were reported to the National Cancer Registry of the GDR from [1961][1962][1963][1964][1965][1966][1967][1968][1969][1970][1971][1972][1973][1974][1975][1976][1977][1978][1979]. Observed cases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…In a 1986 population-based epidemiologic study of the German Democratic Republic, Haas et al 1 reported that the number of meningiomas, acoustic neuromas, and primary malignant intracranial neoplasms diagnosed during pregnancy was less than expected when compared with the general population. With the use of tumor registry data from 1961 to 1979, these investigators identified 17 malignant brain tumors and 3 meningiomas among pregnant women.…”
mentioning
confidence: 99%
“…In a 1986 population-based epidemiologic study of the German Democratic Republic, Haas et al 1 reported that the number of meningiomas, acoustic neuromas, and primary malignant intracranial neoplasms diagnosed during pregnancy was less than expected when compared with the general population. With the use of tumor registry data from 1961 to 1979, these investigators identified 17 malignant brain tumors and 3 meningiomas among pregnant women.…”
mentioning
confidence: 99%
“…2 An epidemiological analysis performed in Germany of all tumours notified through the German Democratic Reporting System 1961-1975 suggested a frequency of 3.6 per 10 6 births which is slightly lower than the background frequency. Of the 29 tumours reported, astrocytoma (9 cases) and glioblastomas (6 cases) were the more frequently observed tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 29 tumours reported, astrocytoma (9 cases) and glioblastomas (6 cases) were the more frequently observed tumours. 2 Haemangioblastomas comprise 1-2% of all intracranial tumours 3 and 7-12% of posterior fossa neoplasms. 3 They often occur sporadically; however, 20-40% of cases occur in association with von Hippell-Lindau disease (VHL).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of malignant brain tumors in pregnancy is 3.6 per million live births (15), and its management is often quite difficult. The treatment of glioma during pregnancy is complex as it may be associated with adverse effects on the fetus.…”
Section: Discussionmentioning
confidence: 99%